On the criteria of transversality and disjointness of nonnegative selfadjoint extensions of nonnegative symmetric operators - Kovalev, Yu. G. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We propose criteria of transversality and disjointness for the Friedrichs and Krein extensions of a nonnegative symmetric operator in terms of the vectors { φ j , j J} that form a Riesz basis of the defect subspace. The criterion is applied to the Friedrichs and Krein extensions of the minimal Schr¨odinger operator A d with point potentials. We also present a new proof of the fact that the Friedrichs extension of the operator A d is a free Hamiltonian.